2020
DOI: 10.1177/2374373519889246
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Analysis of Health-Related Quality of Life in Older Adults With Cancer

Abstract: Objective: The aim of the present study was to evaluate health-related quality of life (HRQoL) changes at 6 to 12 months after cancer diagnosis and to assess the impact of age in older adults with cancer. Methods: A cohort study using patients ≥60 years old diagnosed with cancer. Health-related quality of life scores were calculated according to the European Organisation for Research and Treatment of Cancer questionnaire. Student’s t tests for paired samples and a binomial logistic regression were performed. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…This finding is in agreement with other studies which reported a significantly impaired HRQoL among esophageal cancer patients 21,30–33 . Various studies reported that older, co‐morbid, and advanced‐stage cancer patients had poor HRQoL 15,34–37 . Hence, this high burden of poor HRQoL revealed in our study could be linked to the predominance of co‐morbid and advanced‐stage esophageal cancer patients in our setting.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is in agreement with other studies which reported a significantly impaired HRQoL among esophageal cancer patients 21,30–33 . Various studies reported that older, co‐morbid, and advanced‐stage cancer patients had poor HRQoL 15,34–37 . Hence, this high burden of poor HRQoL revealed in our study could be linked to the predominance of co‐morbid and advanced‐stage esophageal cancer patients in our setting.…”
Section: Discussionsupporting
confidence: 93%
“…21,[30][31][32][33] Various studies reported that older, co-morbid, and advanced-stage cancer patients had poor HRQoL. 15,[34][35][36][37] Hence, this high burden of poor HRQoL revealed in our study could be linked to the predominance of co-morbid and advanced-stage esophageal cancer patients in our setting. In sub-Saharan Africa, cancer care is suboptimal due to the shortage of diagnostic facilities and the high cost of treatment.…”
Section: Determinants Of Hrqol Among Gastrointestinal Cancer Patientsmentioning
confidence: 54%